The Influence of Regional Social Inequality and Labour Market Characteristics on Health - Christiane Gross; Peter Kriwy (Comparative Population Studies, 2013)
The influence of contextual factors on individual health status has been demonstrated by a number of studies even when controlling for the individual socio-economic situation (and other relevant factors). The article examines whether and to what extent variables of the place of residence have an effect on individual health status. We do not only refer to income levels and inequality, but also to effects of the educational level and inequality and the regional unemployment rate. As data basis for the individual level, we use the 2006 wave of the German Socio-Economic Panel Study (SOEP) and add regional information on the aggregate level based on the regional units (Raumordnungsregionen) of the Microcensus of 2005. These data will be analysed using multilevel models. The results reveal that regional educational inequality intensifies the individual educational effect, whereby members of less-educated groups in educationally disparate regions exhibit particularly low health chances. In addition, a high regional unemployment rate intensifies the negative effect of individual unemployment on men’s health.